Acute effects of small-sided games combined with running drills on internal and external loads in young soccer players. - Yusuf Köklü; Hamit Cihan; Utku Alemdaroğlu; Alexandre Dellal; Del Wong (Termedia Publishing House, 2020)
The purpose of this study was to compare the effects of regular small-sided games (SSGreg) and SSGs combined with running drills (SSGcom) on players' internal and external loads. Eighteen young male soccer players (average age: 18.2 ± 0.5 years) participated in 3 vs. 3 and 4 vs. 4 games, under both SSGreg and SSGcom conditions. SSGreg bouts were played for 4 minutes without additional running drills, while SSGcom bouts consisted of 3 min 30 s SSG and 15 s running before and after the bout, making the duration of each bout 4 minutes. During all SSGs, measurements of heart rate (HR) responses as well as distances covered in four different speed zones - walking (WLK), low-intensity (LIR), moderate-intensity (MIR) and high-intensity running (HIR) - were recorded. Technical characteristics were monitored during the SSGs, and the rating of perceived exertion (RPE) and blood lactate (La-) responses were determined at the end of each SSG condition. Compared to the SSGreg in both 3 vs. 3 and 4 vs. 4 formats, the SSGcom condition resulted in higher La- and RPE responses (p < 0.05), greater distance covered at MIR and HIR speeds and greater total distance (p < 0.05). The results of this study show that replacing 30 s within the 4-min bouts of SSGs (both 3- and 4-a-side) by 2 x 15 s of running drills is effective in increasing internal (La- and RPE) and external loads (MIR and HIR) without a significant decrease in total passes and successful passes in young soccer players.